1998
DOI: 10.1073/pnas.95.8.4567
|View full text |Cite
|
Sign up to set email alerts
|

Activating mutations in the extracellular domain of the fibroblast growth factor receptor 2 function by disruption of the disulfide bond in the third immunoglobulin-like domain

Abstract: Multiple human skeletal and craniosynostosis disorders, including Crouzon, Pfeiffer, Jackson-Weiss, and Apert syndromes, result from numerous point mutations in the extracellular region of fibroblast growth factor receptor 2 (FGFR2). Many of these mutations create a free cysteine residue that potentially leads to abnormal disulfide bond formation and receptor activation; however, for noncysteine mutations, the mechanism of receptor activation remains unclear. We examined the effect of two of these mutations, W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
99
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(107 citation statements)
references
References 38 publications
7
99
0
1
Order By: Relevance
“…[2][3][4][5][6] The mechanism for ligand-independent FGF-R dimerization and subsequent activation has been attributed to disruption of intramolecular disulfide bonds in the third immu- noglobulin loop of the FGF-R as a result of a point mutation and loss of an IgIII-associated cysteine residue. [2][3][4][5] Similarly, Robertson and colleagues 36 demonstrated that FGF-R mutations not involving cysteine substitutions may disrupt intramolecular disulfide bonds by altering the conformation of the IgIII domain. Recently, in vitro analysis of the most common Apert mutations (FGF-R2 mutations; Ser252Trp and Pro253Arg) demonstrated increased affinity for FGF-2 ligand as compared to wildtype FGF-R2.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] The mechanism for ligand-independent FGF-R dimerization and subsequent activation has been attributed to disruption of intramolecular disulfide bonds in the third immu- noglobulin loop of the FGF-R as a result of a point mutation and loss of an IgIII-associated cysteine residue. [2][3][4][5] Similarly, Robertson and colleagues 36 demonstrated that FGF-R mutations not involving cysteine substitutions may disrupt intramolecular disulfide bonds by altering the conformation of the IgIII domain. Recently, in vitro analysis of the most common Apert mutations (FGF-R2 mutations; Ser252Trp and Pro253Arg) demonstrated increased affinity for FGF-2 ligand as compared to wildtype FGF-R2.…”
Section: Discussionmentioning
confidence: 99%
“…Several of the mutations in Fgfr1 and Fgfr2 in CS, PS, and JWS constitutively activate the receptor by stabilizing intermolecular disulfide bonds, causing ligand-independent dimerization and signaling (Neilson and Friesel 1995;Wilkie et al 1995a;Galvin et al 1996;Robertson et al 1998). Other mutations are thought to prolong the duration of receptor signaling or alter ligand-binding specificity (Anderson et al 1998;Mansukhani et al 2000;Plotnikov et al 2000;Yu et al 2000;Ibrahimi et al 2001).…”
Section: Fgf Receptor Mutations Induce Craniosynostosis Syndromesmentioning
confidence: 99%
“…Most of these mutations occur in the extracellular and transmembrane regions, and several of these result in the creation or elimination of Cys residues (Webster and Donoghue, 1997b). Either of these processes give rise to free Cys residues that mediate intermolecular disulfide linkage and dimer formation mimicking ligand binding and receptor activation (Neilson and Friesel, 1996;Rousseau et al, 1996;Webster and Donoghue, 1997b;Robertson et al, 1998). Point mutations that do not involve Cys residues have also been reported (Li et al, 1997;Monsonego-Ornan et al, 2000;Winterpacht et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…One group reported that only the myristylated version of the cytosolic domain of K650E-FGFR3 (K/ E-FR3) can transform 3T3 fibroblasts (Webster and Donoghue, 1997a;Robertson et al, 1998). Another group reported that the full-length K/E-FR3 (or Y373C-FR3) could transform 3T3 cells if a different expression system is used (Chesi et al, 2001).…”
Section: Introductionmentioning
confidence: 99%